2001
DOI: 10.1177/00131640121971329
|View full text |Cite
|
Sign up to set email alerts
|

Computerized and Paper-and-Pencil Versions of the Rosenberg Self-Esteem Scale: A Comparison of Psychometric Features and Respondent Preferences

Abstract: Although the use of computerized assessment tools in educational and psychological settings has increased dramatically in recent years, limited information is available about the properties of computerized self-concept measures. The authors evaluated the characteristics of computerized and paper-and-pencil versions of the Rosenberg Self-Esteem Scale (SES)—one of the most widely used self-concept measures in educational and psychological research. Results showed that administration mode (computerized versus pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
43
4
3

Year Published

2002
2002
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(59 citation statements)
references
References 23 publications
8
43
4
3
Order By: Relevance
“…Consistent with previous studies (Hallfors et al, 2000;Rosenfeld et al, 1993;Stanton, 1998;Vispoel, 2000;Vispoel et al, 2001) no significant differences in scores were found between the paper-and-pencil and the computerized versions. The participants who completed the survey on the Web received scores comparable to those of the participants who completed the paper-and-pencil surveys.…”
Section: Implications For Test Scoressupporting
confidence: 92%
“…Consistent with previous studies (Hallfors et al, 2000;Rosenfeld et al, 1993;Stanton, 1998;Vispoel, 2000;Vispoel et al, 2001) no significant differences in scores were found between the paper-and-pencil and the computerized versions. The participants who completed the survey on the Web received scores comparable to those of the participants who completed the paper-and-pencil surveys.…”
Section: Implications For Test Scoressupporting
confidence: 92%
“…To measure global self-esteem, Rosenberg's self-esteem scale (RSE-scale) was utilized at time 1 (Rosenberg, 1972;Vispoel, Boo, & Bleiler, 2001). Global self-assessment was measured using 10 generally formulated items (graded 1-4) (e.g., Sometimes I feel rather worthless; There is nothing I could be proud of; In general, I am quite content with myself).…”
Section: Methodsmentioning
confidence: 99%
“…The research evidences supports H1. Previous findings also had empirical supports that two survey methods did not have marked differences in normal distributions, reliability and validity for the measures of transformation leadership [28], and self-esteem scale [44]. However, some research found differences between proctored internet-based and paper-and-pencil survey in selection contexts; nearly all such differences favor the internet-based survey, even though the items were identical [45].…”
Section: Discussionmentioning
confidence: 85%